A51: C1q Deficiency and Autoimmunity—A Single Centre Experience. Issue 11 (March 2014) - Moraitis, Elena; Eleftheriou, Despina; Cale, Catherine; Pilkington, Clarissa; Brogan, Paul
Abstract : Background/Purpose: C1q deficiency is a rare form of monogenic autoimmune syndrome, associated with predisposition to bacterial infections and systemic lupus erythematosus (SLE) like phenotype. The aim of the study was to describe the clinical characteristics, including presentation, diagnostic features, treatment and outcome in children with primary C1q deficiency from a tertiary paediatric rheumatology service. Methods: Retrospective case notes review of children presenting with C1q deficiency to the Paediatric Rheumatology and Immunology services at Great Ormond Street Hospital for Children between 2002 and 2012, We included in the study all the children with a diagnosis of C1q deficiency, identified on initial screening as having low/absent functional classic complement pathway activity, with subsequent identification of absent C1q levels, in the absence of anti‐C1q antibodies. Where possible, genetic confirmation of a mutation in C1q was obtained. Results: Five children were identified as having primary C1q deficiency; 4 had complete deficiency; 1 had partial deficiency. One case had confirmation of C1q genetic mutations. The median age at disease onset was 12 months (range 6–34 months). Four children presented with autoimmune manifestations: SLE‐like presentation (n = 3); JDM/SLE (juvenile dermatomyositis) overlap syndrome (n = 1). The patient with SLE/JDM phenotype had an extremely severe onset of autoimmune symptomatology, complicated by macrophage activation syndrome. None of the patients had nephritis. The patient with partial deficiency only had recurrent infections. One patient, the sibling of an index case, was asymptomatic at diagnosis but developed an SLE‐like phenotype later on. Four patients had recurrent infections, 3 had severe invasive infections with encapsulated bacteria. Of the 4 patients with SLE symptomatology, none was positive for anti‐dsDNA antibodies, 3 were ANA positive, and 3 were ENA positive. Three patients had transient moderate neutropenia at presentation. Treatment included steroids (n = 3/5) combined with Azathioprine (n = 3/5), Hydroxychloroquine (n = 2/5), or Methotrexate (n = 1/5) and antibiotic prophylaxis for infections (5/5). At median 7.9 (0.7–9.3) years follow up the current status of the patients was: all patients are alive; 3 have absence of symptoms on DMARDs, the patient with partial deficiency is on antibiotic prophylaxis with mild recurrent infections. The patient sibling of an index case who was initially asymptomatic, presented with SLE cutaneous manifestations 6 months after diagnosis, currently still active one month after commencing Azathioprine. None of the patients had a further episode of invasive life threatening infection. Conclusion: These data confirm a wide spectrum of severity and variability in the clinical phenotype of C1q deficiency. Most of the patients present with SLElike cutaneous manifestations, although severe invasive infection is a major concern. Early onset of lupus‐like features with low prevalence of anti‐dsDNA antibodies in the context of recurrent or severe invasive infections may provide a valuable diagnostic clue for the presence of C1q deficiency.